If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(7x+1)-5=23x+39+8x
We move all terms to the left:
6(7x+1)-5-(23x+39+8x)=0
We add all the numbers together, and all the variables
6(7x+1)-(31x+39)-5=0
We multiply parentheses
42x-(31x+39)+6-5=0
We get rid of parentheses
42x-31x-39+6-5=0
We add all the numbers together, and all the variables
11x-38=0
We move all terms containing x to the left, all other terms to the right
11x=38
x=38/11
x=3+5/11
| 4+2/5r=2 | | X/2+7x+90=180 | | 170+40/x=1200 | | (3/5)*e-6=-(2/5)e-3 | | 36^b-3=0 | | 60-3x=40+2 | | -4.41(b−19)=8.82 | | 4r+35(r^2+34)=0 | | 72=2x+10 | | 42-(2x+4)=4(x+6)+x | | 9z+4+28+31=180 | | 3(g+1)−5=4 | | (x+25)+(x•3)=435 | | -4(u-4)=8u+40 | | 4+6x=21 | | |5x+3|=|x+11| | | (3/5)*e-6=(-2/5)e-3 | | p+17.12=2.33 | | 70=10(j+2) | | (3/5)*e-6=-2/5e-3 | | -4(s+19)=-12 | | 4d-12=28 | | (3/5)*e-6=-2/5(e-10)-7 | | 5-2+x=2x-3 | | |-w+6|=-7w | | 14u+-10u+-16u=-12 | | 7(x-4)+7=13x-6(x-3) | | 6x-17+48=90 | | p/3+-8=-6 | | 3x+31+2x-6=90 | | t/3-6=2 | | h/3-9=-7 |